Improving Creative Thinking Skills through Discovery Learning Model in Vocational High Schools - Luthfiyah Nurlaela; Suparji Suparji; IGP Asto Buditjahjanto; Any Sutiadiningsih; Febri Lukitasari (Faculty of Engineering, Universitas Negeri Yogyakarta, 2019)
Several studies indicated the low creative thinking skills of vocational high school students. The objective of this study is to describe the application of discovery learning models to improve the ability of the teachers to manage learning, student activities during the learning process, the student learning outcomes in terms of creative thinking skills, and the student responses to the learning activities. The research subjects were 35 students from the study program of Catering Food Service in a Public Vocational High School, SMK N 6 Surabaya. The lesson plan included the syllabus, learning implementation plans, student activity sheets, and assessment. Meanwhile, the data collection instruments included tests, observations, and questionnaires. The data were analyzed using descriptive statistics and t-test. The results showed that discovery learning model could improve the teacher's ability to manage the learning, students’ activities, learning outcomes of creative thinking skills, and students’ responses.